(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Interior metal complexes appear to be of continued importance owing primarily to their structural and catalytic features and their use in pharmaceutical and laser diagnostics. Anticancer and fungicidal properties were also found. We addressed in our research the synthesis, characterisation, physical and biological studies of bio-ligands. First, we began the general presentation, then in catalysis, synthesis and characterization, physical and biological study we clarified the n- heterocyclic carbonyl ligands, and we tried to understand more about the base ship.